DEVELOPMENT OF MONITORING SYSTEMS: INTEGRATION OF UAVS, GROUND STATIONS, AND NAVIGATION TECHNOLOGIES AT CRITICAL INFORMATION INFRASTRUCTURE - Заїка, Назар; Комаров, Максим; Іщук, Максим; Верховець, Олексій (SWorldJournal, 2024)
The article explores the importance and challenges of ensuring the security of critical information infrastructure (CII). It explains that this includes managing situations of emergency character, physical security systems, and the use of unmanned aerial